Small Things Matter: The 11.6-kDa TraB Protein is Crucial for Antibiotic Resistance Transfer Among Enterococci - Berger, Tamara M.I.; Michaelis, Claudia; Probst, Ines; Sagmeister, Theo; Petrowitsch, Lukas; Puchner, Sandra; Pavkov-Keller, Tea; Gesslbauer, Bernd; Grohmann, Elisabeth; Keller, Walter (Frontiers in Molecular Biosciences, 2022)
Conjugative transfer is the most important means for spreading antibiotic resistance genes. It is used by Gram-positive and Gram-negative bacteria, and archaea as well. Conjugative transfer is mediated by molecular membrane-spanning nanomachines, so called Type 4 Secretion Systems (T4SS). The T4SS of the broad-host-range inc18-plasmid pIP501 is organized in a single operon encoding 15 putative transfer proteins. pIP501 was originally isolated from a clinical Streptococcus agalactiae strain but is mainly found in Enterococci. In this study, we demonstrate that the small transmembrane protein TraB is essential for pIP501 transfer. Complementation of a markerless pIP501∆traB knockout by traB lacking its secretion signal sequence did not fully restore conjugative transfer. Pull-downs with Strep-tagged TraB demonstrated interactions of TraB with the putative mating pair formation proteins, TraF, TraH, TraK, TraM, and with the lytic transglycosylase TraG. As TraB is the only putative mating pair formation complex protein containing a secretion signal sequence, we speculate on its role as T4SS recruitment factor. Moreover, structural features of TraB and TraB orthologs are presented, making an essential role of TraB-like proteins in antibiotic resistance transfer among Firmicutes likely.